THE SOCIAL CONDITIONS OF LEGITIMACY OF NORM MAKING - Martirosyan, Hayk (State and Law, 2022)
The study is dedicated to revealing the peculiarities of legal organization, as well as the analysis and evaluation of the impact of legal organization in that process. Awareness and effective implementation of the legal implementation process is one of the key guarantees for improving the quality of legal acts. The practice of the Republic of Armenia in the mentioned field is lagging behind, based on which proposals are presented within the framework of this study.
Keywords: Law making; lobbying; brain center; legitimacy; sociality; legal awareness; security system